PROPOSED STRATEGY FOR INCREASE NON-AERONAUTIC BUSINESS OF PT ANGKASA PURA II (CASE STUDY : RETAIL AND FOOD & BEVERAGE AT TERMINAL 3) (The Indonesian Journal of Business Administration, 2019)
PT Angkasa Pura II as airport operator in 16 airports in Indonesia in its business of providing services in the aeronautical, non-aeronautical, cargo and other business segments. In 2018, the ratio composition of aeronautical and non-aeronautical revenue is 63.35%: 36.65%. Whereas in the 2016-2020 RJPP document PT Angkasa Pura II has targeted to achieve a non-aeronautical income ratio of 50-60%. The largest non-aeronautical revenue component comes from business concessions obtained from one of the revenue sharing of the tenants. The biggest contribution to revenue sharing came from retail and food & beverages business partners located in Terminal 3 of Soekarno-Hatta Airport with 74.48% of the total revenue sharing. To encourage the increase in the composition of revenue sharing, PT Angkasa Pura II needs to implement strategy adopted from SWOT analysis based on understand the current business situation by analyzing the current conditions of the company internally and externally. This research also focused to measure customer satisfaction with the services provided in the retail and food & beverages business fields, which use the Important Performance Analysis Method based on the five dimensions of service quality contained in Service Quality, namely tangible, empathy, reliability, responsiveness and assurance (TERRA). The research data obtained through the distribution of questionnaires which include questions based on 5 dimensions of service quality, and knowing the factors that most influence the customer to shop in Terminal 3. From the results of the questionnaire data processing, obtained several aspects of the service that must be corrected to be improved in order to meet the customer's expectations. This research finds three factors that need to be concerned to correct rapidly in retails’ service, they are the products’ price, the products’ promotion and easy access for customers to get the information about the product (price, location, promotion etc.)Proposed corrective actions are aligned to the results of strategy analysis obtained through the use of TOWS Matrix. There strategies that might be implemented by PT Angkasa Pura II immediately are: create service blue print for retail business with international standard, enhance the shopping feature in Indonesia Airport application, develop airport e-commerce and pro-hire recruitment with international experiences. More quickly implemented, PT Angkasa Pura II will have chance to achieve the revenue target faster.Keywords: Service Quality, Customer Experience, Cartesian Diagram.